Morphological Evidence for Functional Crosstalk Between Multiple GnRH Systems in the Male Tilapia, Oreochromis niloticus - Ogawa, Satoshi; Parhar, Ishwar (Frontiers in Endocrinology, 2020)
Gonadotropin-releasing hormone (GnRH) is a reproductive neuropeptide, which controls vertebrate reproduction. In most vertebrates, there are more than two GnRH orthologs in the brain. In cichlid fish, the Nile tilapia (Oreochromis niloticus), GnRH1 is the primary hypophysiotropic hormone, while GnRH2 and GnRH3 are non-hypophysiotropic but neuromodulatory in function. Hypophysiotropic GnRH neurons are thought to inter-communicate, while it remains unknown if hypophysiotropic and non-hypophysiotropic GnRH systems communicate with each other. In the present study, we examined interrelationship between three GnRH types using specific antibody raised against their respective GnRH associated peptide (GAP) sequence. Double-immunofluorescence labeling coupled with confocal microscopy revealed that in sexually mature males, GnRH-GAP1-immunoreactive (-ir) processes are in proximities of GnRH-GAP3-ir cell somata in the terminal nerve, while GnRH-GAP1-ir cell somata were also accompanied by GnRH-GAP3-ir processes in the preoptic area. However, such interaction was not seen in immature males. Further, there was no interaction between GnRH-GAP2 and GnRH-GAP1 or GnRH-GAP3 neurons. Single cell gene expression analysis revealed co-expression of multiple GnRH receptor genes (gnrhr1 and gnrhr2) in three GnRH-GAP cell types. In mature males, high levels of gnrhr2 mRNA were expressed in GnRH-GAP1-ir cells. In immature males, gnrhr1 and gnrhr2 mRNAs are highly expressed in GnRH-GAP3-ir cells. These results suggest heterologous interactions between the three GnRH-GAP cell types and their potential functional interaction during different reproductive stages.